Developing Poetry as a Research Methodology with Rarer Forms of Dementia: Four Research Protocols. (17th February 2022) - Camic, Paul M.; Harding, Emma; Sullivan, Mary Pat; Grillo, Adetola; McKee-Jackson, Roberta; Wilson, Lawrence; Zimmermann, Nikki; Brotherhood, Emilie V.; Crutch, Sebastian J.
People living with rarer forms of dementia tend to have progressive cognitive symptoms affecting skills other than memory and/or onset before the age of 65 years. They are often misdiagnosed and due to symptom profile or age of onset, do not usually fit well with care pathways designed for older people with typical Alzheimer's disease or vascular dementia. Although the arts have been increasingly used as interventions to support people with dementia, there is very little attention given to rarer dementia forms in arts and health research or practice. The objective of the present international study seeks to systematically explore four diverse forms of poetry writing within this population through virtual and in-person small and large group formats. Our approach includes investigating poetic processes as methodology through the lens of an arts-based methodological approach in order to explore how poems construct knowledge and a felt experience. We will also use more traditional qualitative approaches to understand the experience of writing, reading and listening to poetry as an intervention that can be used with different rarer forms of dementia. To the best of our knowledge, this will be the first study to explore poetry using multiple research protocols. The results will have implications for methodology development, co-constructed poetic inquiry and multiple opportunities for involving poetry in supporting people with dementia and family members.